Measures of Light in Studies on Light-Driven Plant Plasticity in Artificial Environments - Niinemets, Ülo; Keenan, Trevor (Frontiers in Plant Science, 2012)
Within-canopy variation in light results in profound canopy profiles in foliage structural, chemical and physiological traits. Studies on within-canopy variations in key foliage traits are often conducted in artificial environments, including growth chambers with only artificial light, and greenhouses with and without supplemental light. Canopy patterns in these systems are considered to be representative to outdoor conditions, but in experiments with artificial and supplemental lighting, the intensity of artificial light strongly deceases with the distance from the light source, and natural light intensity in greenhouses is less than outdoors due to limited transmittance of enclosure walls. The implications of such changes in radiation conditions on canopy patterns of foliage traits have not yet been analyzed. We developed model-based methods for retrospective estimation of distance vs. light intensity relationships, for separation of the share of artificial and natural light in experiments with combined light and estimation of average enclosure transmittance, and estimated daily integrated light at the time of sampling (Qint,C), at foliage formation (Qint,G), and during foliage lifetime (Qint,av). The implications of artificial light environments were analyzed for altogether 25 studies providing information on within-canopy gradients of key foliage traits for 70 species x treatment combinations. In experiments with combined lighting, the share of natural light at the top of the plants varied three-fold, and the share of natural light strongly increased with increasing depth in the canopy. The study emphasizes that plant trait vs. light relationships in artificial systems are not directly comparable to natural environments unless modifications in lighting conditions in artificial environments are taken into account.